PENGUATAN KARAKTER RELIGIUS GENERASI ALPHA MELALUI PEMBIASAAN NILAI-NILAI KEAGAMAAN DI MADRASAH IBTIDAIYAH - Muzayyinah, Qotrotunnada; Ainul Yaqin, Firdaus; Fitri Amalia, Nur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the strengthening of religious character among Generation Alpha students through the instillation of religious values at MI Walisongo II. The problem addressed in this study is the suboptimal internalization of religious values, as some students still participate in religious activities primarily due to external pressure. This study aims to analyze the process of strengthening religious character through the instillation of religious values. The method used is descriptive qualitative, employing data collection techniques such as observation, interviews, and documentation involving the principal, teachers, and students. The results of the study indicate that structured habituation activities, such as reciting the Qur’an, performing the dhuha prayer, and daily supplications, are capable of fostering discipline, responsibility, and religious behavior; however, the internalization of values has not yet been fully optimized, necessitating a more consistent and contextual approach tailored to the characteristics of Generation Alpha.